Ensaios de biodegradabilidade aeróbia para apoio à operação de contactor biológico rotatório tratando lixiviados - Soares, Carina Ines dos Santos (Universidade do Vale do Rio dos Sinos, 2013)
This study aims at evaluating the potential for aerobic bio-degradation of landfill leachate and being the support for the operation for the aerobic biological treatment pilot plant. This treatment is a Rotating Biological Contactor (RBC) kind, operated at Unisinos to process the leachate generated at the landfill located in São Leopoldo city - RS. This system has emerged as an alternative for the biological treatment of leachate, because it provides the necessary conditions for the micro-organisms to degrade most part of the pollutants contained in the effluent. The potential for aerobic bio-degradation of leachate was evaluated by testing for aerobic biodegradability using the Zahn-Wellens test. The starting period in RBC was monitored by the analysis of the specific parameters (COD and TOC) and then these results were compared to the results obtained in the tests for aerobic biodegradability. The RBC was operated in two different ways, varying the flow rate and the hydraulic retention time of the leachate system. In the first mode of operation, the flow used was 8.5 L/h and the hydraulic retention times (HRT) was 15 h. In the second mode of operation, the flow used was 5.1 L/h and the hydraulic retention time was 24 hours. The biodegradability tests showed that the average potential for the aerobic bio-degradation of the leachate used in RBC was 44.3% and 54.5% for COD and TOC parameters, respectively. The end of the starting period was in the second mode of operation when the average percentage of removal achieved in the RBC reached 15% and 18% for COD and TOC parameters, respectively.
Aerobic biodegradability tests to support the operation of rotating biological contactor treating leachates
Keywords: Tratamento biológico aeróbio; Lixiviado; Biodegradabilidade; Partida; Aerobic biological treatment; Leachate; Biodegradability; Starting period; ACCNPQ::Engenharias::Engenharia Civil